Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1600-0536.2012.02062.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and impaired health‐related quality of life in patients with occupational hand eczema

Abstract: We found a high prevalence of anxiety and depression in our study population of patients with occupational hand eczema. Preventive measures should consider the psychosocial implications of occupational hand eczema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
85
3
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 31 publications
(76 reference statements)
17
85
3
8
Order By: Relevance
“…In patients with occupational CHE, those with irritant contact dermatitis reported significantly less intense itching than patients with irritant-induced atopic HE [16]. Patients with severe CHE reported more intense itching than patients with non-severe CHE, and individuals with atopic dermatitis had higher visual analogue scale scores for itch than patients with exclusive HE [16]. This confirms our results showing a significant association between atopic diathesis and severe itch.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In patients with occupational CHE, those with irritant contact dermatitis reported significantly less intense itching than patients with irritant-induced atopic HE [16]. Patients with severe CHE reported more intense itching than patients with non-severe CHE, and individuals with atopic dermatitis had higher visual analogue scale scores for itch than patients with exclusive HE [16]. This confirms our results showing a significant association between atopic diathesis and severe itch.…”
Section: Discussionsupporting
confidence: 81%
“…Results from our multivariate analysis did not show a significant difference between the presence of itch and sex, meaning that women and men with CHE are equally affected by itch. This is in contrast to results from most of the studies on itch considering sex [4,5,15,16,17]. A cross-sectional study with adults on self-reported skin morbidity in Oslo, Norway showed that women reported itching more often than men throughout all age groups [15].…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Svaki od tih instrumenata sastavljen je od upitnika, sa različitim pitanjima. U istraživanju, instrumenti kvaliteta života specifični za dermatologiju, korišćeni su kod pacijenata sa jednim oboljenjem kože ili uopšte sa kožnim bolestima [7,8,9,10,11,12]. I pored postojanja publikovanih podataka o valjanosti i pouzdanosti za ove instrumente, još uvek ne postoji saglasnost o tome, da li u okviru jedne studije treba koristiti samo jedan ili dva instrumenta za kvalitet života [13,14,15,16].…”
Section: Uvodunclassified